ANALISIS PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM PADA SEKTOR PERTAMBANGAN BATU BARA - Larasati Kusuma Wardani; Gideon Setyo Budiwitjaksono (Jurnal Proaksi, 2021)
The current condition of the capital market is full of uncertainty, which can be seen from fluctuations in stock prices and Returns. The volatility of the company’s stock price can indicate that investors have not obtained optimal stock Returns. This study aims to examine the effect of profitability and Leverage on stock Returns in the coal mining sector listed on the IDX in 2017-2019. This research uses associative research with a quantitative approach. The population used is all coal mining sectors listed on the IDX in 2017-2019 and the sample is used for purposive sampling that is 16 companies. Secondary data is used by accessing the official IDX website then downloading the annual financial reports of the coal mining sector for 2017-2019. Multiple linear regression was used as analysis in this study with statistical software. The results of the study state that profitability and Leverage have no effect on stock Returns in the coal mining sector which is listed on the Indonesia Stock Exchange in 2017-2019. Keywords: Leverage, Profitabilitas, Return Saham